1875 Va. Acts 164, ch. 162 - (:unkn) unknown (My University, 1875)
Approved a property tax on all males over the age of twenty-one on the aggregate value of all rifles, muskets, and other firearms, Bowie-knives, and all weapons of a similar kind.
Keywords: TAX - PROPERTY OR SALES